REAKSI PASAR MODAL TERHADAP PERISTIWA MERGER DAN AKUISISI (Studi pada Industri Perbankan Indonesia yang Listing di Bursa Efek Indonesia periode 2010-2015) - Maharani, Anindya Kusuma (Jurnal Ilmiah Mahasiswa FEB, 2017)
Merger and acquisition is one of important strategies for companies to develop and to improve their efficiency by creating synergy, reducing costs, acquiring assets, and expanding market coverage. This study tries to identify the difference of average abnormal return (AAR) and average trading volume activity (ATVA) before and after the merger and acquisition by Indonesian banking companies listed in the Indonesia Stock Exchange in the period of 2010-2015.This research uses event study and market model method. Through purposive sampling, this study has selected five Indonesian banking companies listed in the Indonesia Stock Exchange that has carried out merger and acquisition practice during 2010-2015 as the sample. The observation periods are ten days prior to, one day during, and 60 days following the merger and acquisition announcement. The data were collected through documentation. The research variables are Abnormal Return and Trading Volume Activity assessed using Paired sample t-Test.The result of the first hypothesis testing shows that there are significant differences in the AAR of stocks before and after merger and acquisition events. The result of the second hypothesis testing shows that there are significant differences in the ATVA before and after merger and acquisition events. Those results indicate significant market reaction on merger and acquisition announcements. This means that merger and acquisition practices carried out by banking companies during 2010-2015 contain information for capital market.Keywords: capital market, merger and acquisition, event study, abnormal return, trading volume activity